Acute and longitudinal changes in motor cortex function following mild traumatic brain injury. (September 2014) - Miller, Nick R.; Yasen, Alia L.; Maynard, Logan F.; Chou, Li-Shan; Howell, David R.; Christie, Anita D.
Abstract Primary objective: To evaluate excitability and inhibition of the motor cortex acutely and longitudinally following mild traumatic brain injury (mTBI). Research design: A longitudinal paired case-control design was used to examine cortical excitability and inhibition in 15 adults who had sustained an mTBI (mean age = 20.8 ± 1.2 years) and 15 matched control participants (mean age = 21.1 ± 1.3 years). Methods and procedures: Participants visited the lab within 72 hours of injury and again at 1, 2, 4 and 8 weeks post-injury. During each visit, transcranial magnetic stimulation was used to examine resting motor threshold (RMT), motor evoked potential peak-to-peak amplitude (MEPamp) and cortical silent period (CSP) duration of the first dorsal interosseous muscle. Main outcomes and results: There were no differences between groups in RMT (p = 0.10) or MEPamp (p = 0.22) at 72 hours post-injury or across the 2-month testing period (p ≥ 0.68), indicating similar cortical excitability. However, the CSP duration was higher in individuals with mTBI, indicating greater intra-cortical inhibition compared with the control group at 72 hours post-injury (p = 0.03) and throughout the 2 months of recovery (p = 0.009). Conclusions: mTBI appeared to have little effect on cortical excitability, but an acute and long-lasting effect on intra-cortical inhibition.